1082 Using an Electronic Health Record (EHR) to Collect and Use Quality-Of-Life Data for AASM Process and Outcomes Quality Measures. (27th April 2018) - Staley, B; Keenan, B T; Simonsen, S; Warrell, R; Schwab, R; Breen, M; Bae, C; Pack, A; Schutte-Rodin, S
Abstract: Introduction: Quality measures (QM) were developed by AASM in 2015 in order "to improve the quality of care for patients with sleep disorders" (AASM website) at sleep clinics and labs. Quality-of-life (QOL) measures are included as process and outcomes QMs for several sleep disorders. The Penn Sleep Center now collects the Epworth Sleepiness Scale (ESS), FOSQ-10 and PROMIS-10 Physical and Mental domains using an integrated EHR-based sleep questionnaire. Methods: EHR-based questionnaires are auto-linked to all new and return office visits and available for patients to complete from home or mobile using an EHR patient portal, or on waiting room tablets as part of the standard visit check-in process. EHR-based data were auto-exported, de-identified, and analyzed for benchmark QM. The aim was to determine the percentage of QOL data collected for all patients with sleep disorders at the Penn Sleep Center, and to evaluate QOL differences for new and returning patients. Results: Of 2, 844 patients seen over the 3 month study period, 700 (25%) were new and 2144 (75%) were returning patients. Nearly 80% of patients completed QOL metrics and >90% completed ESS. Each metric was better in all returning compared to all new patients, including the ESS (8.26 ± 5.26 vs. 9.03 ± 5.51, p=0.0016), FOSQ-10 (30.42 ± 7.56 vs. 29.16 ± 7.53, p=0.0003), and the PROMIS-10 Mental (13.03 ± 3.32 vs. 12.39 ± 3.36, p<0.0001) and Physical (13.87 ± 3.33 vs. 13.40 ± 3.25, p=0.0024) scores. Conclusion: Benchmark QOL data were successfully collected and exported using a recently developed EHR-based questionnaire in nearly 80% of patients. There were improved values for each metric in returning patients when compared to new patients during the same period. Obtaining these metrics systematically in a large majority of patients will allow for robust future analyses evaluating responses of QOL measures with therapy and comparisons between change of QOL for specific sleep disorders and therapies and for patient subgroups of interest. Support (If Any): none.